City Employee Bargaining with a Divided Management - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "City Employee Bargaining with a Divided Management" by Thomas A. Kochan.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z